Interior Chinatown [book club bag] - Yu, Charles, 1976- (Pantheon Books, 2020)
"Willis Wu doesn<U+2019>t perceive himself as a protagonist even in his own life: He<U+2019>s merely Generic Asian man. Sometimes he gets to be Background Oriental Making a Weird Face or even Disgraced Son, but he is always relegated to a prop. Yet every day he leaves his tiny room in a Chinatown SRO and enters the Golden Palace restaurant, where Black and White, a procedural cop show, is in perpetual production. He<U+2019>s a bit player here, too, but he dreams of being Kung Fu Guy<U+2014>the most respected role that anyone who looks like him can attain. At least that<U+2019>s what he has been told, time and time again. Except by one person, his mother. Who says to him: Be more.."--